Selection of environmental temperature by the yellow scorpion Tityus serrulatus Lutz & Mello, 1922 (Scorpiones, Buthidae) - K. Hoshino; A. T. V. Moura; H. M. G. De Paula (Journal of Venomous Animals and Toxins including Tropical Diseases, 2006)
The preferred temperature of the yellow scorpion Tityus serrulatus was investigated since its dispersion is a matter of concern. Adult T. serrulatus, weighing 1.24 + 0.20 g (mean + sd) and with a standard length of 59.3 + 2.5 mm, were used. A metallic corridor (120 cm long, 5 cm large and 10 cm high) with thermal gradient ranging from 0°C to 40°C was used. Tityus serrulatus chose and stayed in temperatures ranging from 14°C to 38°C when safe conditions were offered (dark and thigmotactic stimuli). The number of animals that remained in the 11°C-20°C, 21°C-30°C, and 31°C-40°C temperature zones were 8, 8, and 9, respectively. The chi-square test (degree of freedom = 2) showed that differences were not significant (p>0.05). Some animals moved to lower temperature areas (less than 8°C) when the corridor was completely illuminated and thigmotactic stimuli were absent, which led the animals to present a torpor state. It is concluded that T. serrulatus does not select a specific environmental temperature. Associated with the capacity of temporally surviving at low temperatures, this species seems to be highly adaptable to different thermal zones.